Effect of sodium bicarbonate on the physicochemical properties of fermented rice flour and quality characteristics of fermented semi-dried rice noodles - Xiao, Wen; Ding, Yuqin; Cheng, Ying; Xu, Sili; Lin, Lizhong (Frontiers in Nutrition, 2023)
Considering the effect that fermentation can improve the quality of rice noodles, and given that fermented rice noodles usually have a significantly acidic taste that is not generally acceptable to consumers, this study aimed to neutralize or eliminate the acidic taste of fermented rice noodles by adding sodium bicarbonate, and improve the quality of fermented rice noodles. The physicochemical properties of fermented rice flour and quality characteristics of fermented semi-dried rice noodles were investigated in this study in relation to the addition of sodium bicarbonate (0~0.5%, w/w). With the increase of sodium bicarbonate addition, the pH value was increased, and lipid and protein content were decreased in rice flour. Meanwhile, thermal properties and farinograph properties showed that the pasting temperature, dough water absorption, dough development time and dough stability time of rice flour increased with the addition of sodium bicarbonate. Pasting properties and rheological properties results showed that a small amount of sodium bicarbonate (0~0.1%) could increase the pasting viscosity, storage modulus (G′), and loss modulus (G") of rice flour. Additionally, the hardness and chewiness of semi-dried rice noodles increased with the addition of sodium bicarbonate from 0 to 0.1%. With the addition of a small amount of sodium bicarbonate (0~0.1%), x-ray diffraction showed that it could increase the crystallinity of semi-dried rice noodles. Low-field nuclear magnetic resonance showed that A21 increased, and A22 and A23 decreased in semi-dried rice noodles. Scanning electron microscope showed that it could enhance the starch-protein interaction and starch-protein formed an ordered and stable network structure. Finally, the principal component analysis showed that the chewiness, texture and eating quality of semi-dried rice noodles were the best with the addition of sodium bicarbonate at 0.1%. This study provides practical value for the application of alkali treatment in rice products and provides a reference for the improvement of related rice noodles products.